The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2004
DOI: 10.1056/nejmoa041018
|View full text |Cite
|
Sign up to set email alerts
|

Catheter Ablation for Atrial Fibrillation in Congestive Heart Failure

Abstract: Restoration and maintenance of sinus rhythm by catheter ablation without the use of drugs in patients with congestive heart failure and atrial fibrillation significantly improve cardiac function, symptoms, exercise capacity, and quality of life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
307
5
16

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 784 publications
(341 citation statements)
references
References 35 publications
12
307
5
16
Order By: Relevance
“…During the past few decades, several invasive and noninvasive hemodynamic studies have shed light on the role played by atrial systole and normal sinus rhythm in maintaining adequate cardiac output, particularly during exercise and in patients with heart failure 5, 8, 17, 20, 21, 22, 23. Inadequate cardiac output during AF has been attributed to several mechanisms, including loss of atrial systole, irregular ventricular rhythm with beat‐to‐beat variability, and impaired ventricular filling time 9, 17, 21, 22.…”
Section: Discussionmentioning
confidence: 99%
“…During the past few decades, several invasive and noninvasive hemodynamic studies have shed light on the role played by atrial systole and normal sinus rhythm in maintaining adequate cardiac output, particularly during exercise and in patients with heart failure 5, 8, 17, 20, 21, 22, 23. Inadequate cardiac output during AF has been attributed to several mechanisms, including loss of atrial systole, irregular ventricular rhythm with beat‐to‐beat variability, and impaired ventricular filling time 9, 17, 21, 22.…”
Section: Discussionmentioning
confidence: 99%
“…The initial study to address this important topic was published in 2004. 232,1042 This study examined the role of catheter ablation in 58 patients with HF with an EF of less than 45% and 58 controls. During a mean follow-up of 12 ± 7 months, 78% of patients with HF and 84% of controls remained in sinus rhythm.…”
Section: Outcomes Of Af Ablation In Populations Not Well Represented mentioning
confidence: 99%
“…1193 Injury to the left PN during isolation of a persistent left SVC was not observed in several case series using RF energy. 232,1042,1194,1195 Very rarely, ablation at the roof of the LAA can result in left PN damage 1184 ; however, it was not observed in a large study in which LAA isolation was performed using RF ablation. 532,533 The incidence of PN palsy is 0.17%–0.48% with PV antrum isolation using RF ablation, even though the PN is found within the typical WACA and carina lines of the right-sided PVs in 30% of patients.…”
Section: Section 10: Complicationsmentioning
confidence: 99%
“…In addition, results from several trials suggest that early restoration and long-term maintenance of sinus rhythm provides considerable benefits, including improvement in cardiac function and quality of life and a lower risk of death in select populations. [27][28][29][30] Furthermore, a recent study in patients with long-standing PeAF suggested that transformation from nonparoxysmal to PAF after catheter ablation may …”
Section: Af Progression and Types Of Afmentioning
confidence: 99%